Blockage of LMP1-modulated store-operated Ca2+ entry reduces metastatic potential in nasopharyngeal carcinoma cell. Issue 2 (1st May 2015) - Wei, Jiazhang; Zhang, Jinyan; Si, Yongfeng; Kanada, Masamitsu; Zhang, Zhe; Terakawa, Susumu; Watanabe, Hiroshi
Highlights Two in vivo models, mice and transgenic zebrafishes, were employed into the present study. The circulating LMP1-expressing cells arrested in a small-caliber vessel actively mobilized surrounding endothelial cells. We propose that EBV-encoded LMP1 endows NPC cell with aggressive properties by boosting SOCE.